PENGEMBANGAN APLIKASI PENGGAJIAN UPAHQU BERBASIS ERP (Enterprise Resource Planning) DI PT.ANDROMEDIA - Diva Aulia Shafira, (2022)
Payroll system is one of the important things in the company's financial activities. PT.Andromedia which is an IT company requires a computerized payroll system because previously it was still using a manual payroll system. To meet the needs of the payroll system, it is necessary to develop a payroll system. In addition to preventing payroll errors, it also helps companies in managing employee payroll easily. In conducting the analysis, researchers used the PIECES method in determining system requirements. In addition, in developing the system, researchers used the Agile Scrum method to adjust the needs of the system developed through interviews with potential users. Applications are made using Visual Studio Code in coding and using the React framework, Laravel Framework, Tailwind framework to assist researchers in creating attractive displays. Researchers also use Prismabase (Prisma Schema) in storing data into the database . It is hoped that this system can be the right alternative to save time and energy and make it easier for PT. Andromedia staff to make payroll.